Discovery of Ancient Volcanoes in the Okhotsk Sea (Russia): New Constraints on the Opening History of the Kurile Back Arc Basin - Werner, Reinhard; Baranov, Boris; Hoernle, Kaj; van den Bogaard, Paul; Hauff, Folkmar; Tararin, Igor (Geosciences, 2020)
Here we present the ﬁrst radiometric age and geochemical (major and trace element and isotope) data for samples from the Hydrographer Ridge, a back arc volcano of the Kurile Island Arc, and a newly discovered chain of volcanoes (“Sonne Volcanoes”) on the northwestern continental slope of the Kurile Basin on the opposite side of the arc. The 40 Ar/ 39 Ar age and geochemical data show that Hydrographer Ridge (3.2–3.3 Ma) and the “Sonne Volcanoes” (25.3–25.9 Ma) have very similar trace element and isotope characteristics to those of the Kurile Island Arc, indicating derivation from a common magma source. We conclude that the age of the “Sonne Volcanoes” marks the time of opening of the Kurile Basin, implying slow back arc spreading rates of 1.3–1.8 cm/y. Combined with published data from the Kurile fore arc, our data suggest that the processes of subduction, Kurile Basin opening and frontal arc extension occurred synchronously and that extension in the rear part and in the frontal part of the Kurile Island Arc must have been triggered by the same mechanism.